FREQUENCY OF GASTRIC CANCER, ENDOSCOPICAL AND HISTOLOGICAL- FEATURES IN ERZURUM REGION - N. OKÇU; M. Derya ONUK; E. AKARSU; M. GÜNDOĞDU; C. GÜNDOĞDU; Tahir BURAN (Turkish Journal of Gastroenterology, 2020)
-